(3GdfXGe GdbGfhfi dJfajP YbO GdHjY GdJLGQi GdOhdi h GdMjdhdI Ohf aSNg (B/ s - (3eMeO UdGM YHOGddg eMeOs; (3SejMI eUWai GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3aj Xd GfJTGQ hSGFd GdJcfhdhLjG GdMOjKI, h efgG JbOe hSGFd GdGJUGdGJ GdMOjKI, bO CUHM GdYGde CTHg HGdbQjI GdUZjQI, h bO CUHM EHQGe YbhO GdHjhY GdOhdjI ddHVGFY CSQY ef Ci hbJ eVj, h dPG abO GfJTQJ YbhO GdHjhY GdOhdjI HUhQI cHjQI aj GdMjGI GdjhejI, h CUHMJ aj RjGOI eSJeQI, NGUI Cf cGaI GdTYhH bO CUHMJ aj MGLI eSJeQI Edi JHGOd GdKbGaGJ h GdeYGQa GdafjI, hGdJcfhdhLjG, hGdHVGFY GdeYjTjI(B. (3Ef GfJbGd GdedcjI ef GdHGFY Edi GdeTJQi dG jJQJH Ydjg chf GdeTJQj jYO MGFRkG Edi GdeHjY heSjWQG Ydjg SjWQI cGedI Jecfg ef GdJUQa ajg h ef EYGOI HjYg eQI CNQj, adPG cGf dGHO Cf jchf gfGdc GdJRGe jdJRe Hg GdHGFY jecf GdeTJQi ef GdbjGe HJdc GdCYeGd, adPG cGf GdGdJRGe HGdJSdje ddHVGFY jYO ef Cge GdGdJRGeGJ GdJj jdJRe HgG GdHGFY, h de JNd GdJTQjYGJ GdOhdjI h cPG GdJTQjY GdeUQi ef EdRGe GdHGFY Hg, h fXQkG dYXe gPG GdOhQ GdPi jDOjg JfajP gPG GdGdJRGe(B. (3Ef GdJSdje bO YQa HYOI JYQjaGJ, h EffG Sha fdbj GdVhA Ydi Jdc GdJYQjaGJ ShGA aj GJaGbjI (B{u(306A4(B}(3jjfG(B1980(3Ch aj GdJTQjY GdeUQi(B. (3Ef GJaGbjI (B{u(306A4(B}(3jjfG(B1980 (3de JYQa GdJSdje(B. (3h Pdc Ydi YcS GJaGbjJj dGgGi (B1964. (3dcf JYQja GdJSdje aj GJaGbjI(B1980(3dG jNQL Yf GdJYQja GdPi YQa Hg GdeTQY GdeUQj GdJSdje, h WHbkG dPdc jchf JSdje GdHVGFY ZjQ GdeWGHbI jYO JSdjekG ai GJaGbjI (B{u(306A4(B}(3jjfG(B1980 (3HNdGa GJaGbjI dGgGi(B1964, (3h jchf GdeTJQi dg GdMb aj eeGQSg GdLRGAGJ GdeJGMI dgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi , (B2018 s
(3HHdjhLQGajG(B: (3UaMGJ (B294-304s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3eHGOF JfajP YbO GdHjY GdOhdj ddHVGFYs; (3GdJRGeGJ GdHGFY aj YbO GdHjY GdOhdj ddHVGFYs; (3GdJRGeGJ GdeTJQj aj YbO GdHjY GdOhdj ddHVGFYs; (3GdNdd aj JfajP YbO GdHjY GdOhdj ddHVGFYs; (3GdeNGdaI GdLhgQjI aj JfajP YbO GdHjY GdOhdj ddHVGFY aj GJaGbjI ajjfG (B1980s; (3GdeNGdaI GdLhgQjI aj JfajP YbO GdHjY GdOhdj ddHVGFY aj GdJTQjY GdeUQjs; (3GdLRGAGJ GdeJQJHI Ydi GQJcGH eNGdaI LhgQjI aj JfajP YbO GdHjY GdOhdj ddHVGFY s; (3aSN YbO GdHjY GdOhdj ddHVGFYs; (3GdJfajP GdYjfj dYbO GdHjY GdOhdj ddHVGFYs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs